Belcher Islands, Northwest Territories / compiled, drawn, and printed at the Office of the Surveyor General, 1933, by the Topographical Survey of Canada - Canada. Hydrographic and Map Service (Ottawa, Canada : Topographical Survey, Department of the Interior, 1933)
Relief shown by spot heights Includes 3inset maps and notes Belcher Islands, Northwest Territories -- [Location map] -- King George Islands [enlargement] -- The Declination of the compass needle, January 1933 Color 1:253,440. 1 in. = 4 miles